2007
DOI: 10.1007/s00423-006-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative early and midterm results of open juxtarenal and infrarenal aneurysm repair

Abstract: Open aortic surgery for JRA with the need for suprarenal cross-clamping shows a slightly elevated in-hospital mortality rate without statistical significance and equal midterm mortality results in comparison with infrarenally clamped aortic aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…The overall increase in complications associated with CAA was influenced by cardiac, pulmonary, and renal complications with similar rates reported by other investigators. [11][12][13][14][15][25][26][27] This is consistent with the theoretic increase in risk associated with the technical challenges of complex aneurysm repair, a more proximal clamp application and the attendant renal and/or visceral ischemia. Patients undergoing VVR had the highest frequency of major complication, which were also influenced by cardiac, pulmonary, and renal complications (Table VI).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The overall increase in complications associated with CAA was influenced by cardiac, pulmonary, and renal complications with similar rates reported by other investigators. [11][12][13][14][15][25][26][27] This is consistent with the theoretic increase in risk associated with the technical challenges of complex aneurysm repair, a more proximal clamp application and the attendant renal and/or visceral ischemia. Patients undergoing VVR had the highest frequency of major complication, which were also influenced by cardiac, pulmonary, and renal complications (Table VI).…”
Section: Discussionsupporting
confidence: 77%
“…10 Many single center experiences from high volume centers have reported low mortality and moderate morbidity for complex aneurysm repair; however, these reports are limited by cohort size, and inclusion of data spanning decades of experience. [11][12][13][14][15][16] Jongkind et al 17 recently published a systematic review on outcomes of juxtarenal aneurysm repair. This review collated outcomes from 21 published reports with a total of 1256 patients and concluded that juxtarenal aneurysm repair can be performed with acceptable mortality (2.9%) and that postoperative renal dysfunction is common.…”
mentioning
confidence: 98%
“…30 Twenty-three studies described combined results of JAA and SAA repair or surgery for occlusive disease. From 19 studies, specific data on mortality or new onset of dialysis after non-ruptured open JAA repair could not be retrieved and were excluded, [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] resulting in 21 articles to be included in the systematic review. [1][2][3][4][5][6][7][8][9][10]15,[50][51][52][53][54][55][56][57][58][59] The chance adjusted interreviewer agreement for study eligibility (kappa) was 0.77.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] The incidence of renal failure after suprarenal clamping has been shown to depend on clamp time and is estimated at about 20%, with 3% to 4% requiring permanent dialysis. 1,[15][16][17] The question of nephroprotection as a possible adjunct to improve outcome arises.…”
mentioning
confidence: 99%
“…[1][2][3] In the era of endovascular aneurysm repair (EVAR), the relative number of patients presenting for open conventional surgery with a hostile proximal anatomy and frequently pre-existing reduced renal function, increases steadily. [4][5][6] This is because of a number of late conversions, but more important, because of the decreased reluctance to operate on severely comorbid or elderly patients despite clearly rising rates of complications with age.…”
mentioning
confidence: 99%